Behavioural effects of cage systems on the G93ASuperoxide Dismutase 1 transgenic mouse model for amyotrophic lateral sclerosis. (4th June 2021) - Guerra, Stefan; Chung, Roger; Yerbury, Justin; Karl, Tim
Abstract: Environmental factors inherent to animal facilities can impact on the neuro‐behavioural phenotype of laboratory mice and genetic mouse models for human diseases. Many facilities have upgraded from traditional 'open filter top' cages (FT) to individually ventilated cage (IVC) systems, which have been shown to modify various behavioural responses of laboratory mice. Importantly, the impact of IVC housing on the G93A superoxide dismutase 1 mouse model of amyotrophic lateral sclerosis (ALS) is currently unknown. Male and female wild type‐like (WT) and heterozygous SOD1 G93A mice were group‐housed in FT or IVC systems from PND 30 ± 5 onwards. Body weight and motor function were assessed weekly from 15 weeks onward. Mice were also tested for cognitive abilities (i.e., fear conditioning and social recognition memory) and sensorimotor gating (i.e., prepulse inhibition: PPI). SOD1 G93A mice lost body weight, and their motor function degenerated over time compared with control littermates. Motor impairments developed faster when SOD1 G93A females were housed in IVCs. Context and cue freezing were increased in SOD1 G93A females compared with controls, whereas all SOD1 G93A mice exhibited lower acoustic startle and PPI than WT mice. IVC housing led to an increase in cue freezing in males and reduced the severity of PPI deficits in SOD1 G93A females. Overall, IVC housing impacted moderately on the SOD1 G93A phenotype but central behavioural deficits were still evident across housing conditions. Nonetheless, our findings indicate the importance of assessing the effect of cage system in genetic mouse models as these systems can modulate the magnitude and onset of genotypic differences. Abstract : Motor impairments developed faster and severity of PPI deficits was reduced in SOD1 G93A females when housed in IVCs.